2002
DOI: 10.1046/j.1365-2230.2002.01050.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of 18 children with scabies or cutaneous larva migrans using ivermectin

Abstract: In addition to onchocerciasis and other filarial diseases, ivermectin has been used for the treatment of scabies, head lice, larva migrans and gnathostomiasis. However, there is concern regarding the safety of its use in children under 5 years of age or weighing less than 15 kg. We present our experience in 18 children (aged 14 months to 17 years), with scabies or cutaneous larva migrans successfully treated with ivermectin. They included four cases of crusted scabies associated with immunosuppression and seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…Indeed, we found only one randomized control trial, on 110 children, aged from 6 months to 14 years, who were treated with ivermectin for scabies, 6 and one case series of 18 children, aged from 14 months to 16 years, who were treated with ivermectin for scabies or cutaneous larva migrans. Indeed, we found only one randomized control trial, on 110 children, aged from 6 months to 14 years, who were treated with ivermectin for scabies, 6 and one case series of 18 children, aged from 14 months to 16 years, who were treated with ivermectin for scabies or cutaneous larva migrans.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found only one randomized control trial, on 110 children, aged from 6 months to 14 years, who were treated with ivermectin for scabies, 6 and one case series of 18 children, aged from 14 months to 16 years, who were treated with ivermectin for scabies or cutaneous larva migrans. Indeed, we found only one randomized control trial, on 110 children, aged from 6 months to 14 years, who were treated with ivermectin for scabies, 6 and one case series of 18 children, aged from 14 months to 16 years, who were treated with ivermectin for scabies or cutaneous larva migrans.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies indicated that ivermectin was administered between meals,7 15 two studies stated it was given with milk or food1 2 and the remaining studies did not provide information on the timing of administration. The prescribed dose of ivermectin was similar across all studies, with seven of the nine studies prescribing 200 µg/kg, one study giving a range of 150–200 µg/kg (indication: scabies or cutaneous larva migrans)2 and the last study used a dose of 175 µg/kg (indication: meningoencephalitis secondary to Baylisascaris procyonis infection) 6. A single dose of ivermectin was prescribed in most studies; however, two studies prescribed a second dose to all children1 10 and an additional two children in separate studies were given a second dose due to ongoing symptoms 2 7…”
Section: Commentarymentioning
confidence: 95%
“…Ivermectin (one to two 12-mg doses) has yielded cure rates ranging from 77% and 100% [6••,50,54]. A single dose of ivermectin 150 µg/kg in children was welltolerated and resulted in 100% cure rate [55].…”
Section: Cutaneous Larva Migransmentioning
confidence: 99%